Induction of resistance to bitter rot in apples by the use of elicitors in the postharvest - Alamino, Douglas Alvarez; Cabral, Vagner Bandeira; Danner, Moeses Andrigo; Marchese, José Abramo (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the effect of the protein elicitors acibenzolar‑S‑methyl (ASM) and harpin, applied during the postharvest handling, on a systemic resistance induction to bitter rot on apple. Mechanical injury were made on ’Royal Gala’ apples, followed by application of the elicitors. Twelve hours later, inoculation of Colletotrichum gloeosporioides was performed. Seventy‑two hours later, evaluations were done for the injured area and the number of spores, and tissue samples were taken to determine the contents of proteins, total and reducing sugars, total phenolics, and the activity of phenylalanine ammonia‑lyase, superoxide dismutase, catalase, peroxidase, and ascorbate peroxidase enzymes. Harpin, and to a lesser extent, ASM increased the activity of peroxidase enzyme and, in consequence, reduced the injured area and sporulation caused by C. gloeosporioides in apples. These elicitors could be used as a control tool in the integrated management of bitter rot in the postharvest handling of ’Royal Gala’ apples.